PENERAPAN MODEL TALKING CHIPS DALAM MENGIDENTIFIKASI UNSUR-UNSUR INTRINSIK TEKS DRAMA - Rima Novpria; Warni Warni; Oky Akbar (Universitas Negeri Makassar, 2024)
This study aims to describe the steps and results of the application of the talking chips model in identifying the intrinsic elements of drama text for students of class VIII D SMP Negeri 3 Jambi City. This research uses qualitative methods and descriptive research types. The data source of this research was students of class VIII D SMP Negeri 3 Jambi City. The data in this study are the steps of the talking chips learning model and the results of student assessment in identifying the intrinsic elements of the text. The results of this study are the lesson plans made by researchers are appropriate and implemented when applying the talking chips learning model in identifying the intrinsic elements of drama texts. The conclusion shows that the implementation of the talking chips model in identifying the intrinsic elements of drama text has been carried out.